Shakespeare and Donne : Generic Hybrids and the Cultural Imaginary - Anderson, Judith H. (Book collections on Project MUSE., 2013)
Shakespeare and Donne are themselves hybrids who crossed generic and social boundaries and also shared a contemporary urban space and roots in the old religion. Centring on cross-fertilisation between these authors' writings, the chapters in this volume examine relationships that are broadly cultural, theoretical, and imaginative. They emphasise the intersection of physical or material dimensions of experience with nonphysical and transcendent ones, whether these are moral, intellectual, or religious. They also juxtapose lyric and sermons interactively with narrative and plays.